Analysing the supervised learning methods for prediction of healthcare data in cloud environment: A Survey - Annigeri, NM; Shetty, S; Patil, AP (International Journal of Computer Sciences and Engineering, 2025)
In the present era of massive usage of computers, an enormous set of data is being generated from different organizations each day, each hour and each second. This data would be of prodigious use to a diverse set of people based on their needs. Predictive analysis is a process of analysing data and identifying the different patterns in it, so as to predict the occurrence of these patterns in future. The predicted output can help plan a new strategy and adopt innovative solutions for the decision making. This paper attempts to analyse the various predictive models which are applied in the healthcare domain. These models are analysed in depth and will be proposed to be available on the cloud environment in future and can be accessed by those concerned for potential analysis.